2016
DOI: 10.3758/s13421-016-0601-3
|View full text |Cite
|
Sign up to set email alerts
|

A fresh pair of eyes on prospective memory monitoring

Abstract: Remembering to complete one's future intentions is termed prospective memory. We employed a new eyetracking paradigm to concretely observe the impact of environmental cues on strategic monitoring within a visual prospective memory task. Participants worked on a continuous living-count task comprising images, while simultaneously being asked to respond to a prospective memory target when it appeared. Importantly, the prospective memory target appeared in a different area of the participant's visual field than d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…Apart from the classical measures of monitoring via ongoing task measures, we additionally measured monitoring by the proportion of eye movements to the respective target region (see also Shelton and Christopher, 2016). As only a handful of studies investigated PM target monitoring using eye tracking, some scepsis remains whether eye movements can be considered a valid indicator of strategic monitoring and are not simply driven by involuntary reflexes to e.g., salient stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Apart from the classical measures of monitoring via ongoing task measures, we additionally measured monitoring by the proportion of eye movements to the respective target region (see also Shelton and Christopher, 2016). As only a handful of studies investigated PM target monitoring using eye tracking, some scepsis remains whether eye movements can be considered a valid indicator of strategic monitoring and are not simply driven by involuntary reflexes to e.g., salient stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…However, large ongoing task measures do not necessarily relate to high monitoring, as intention maintenance (Ballhausen et al, 2017), general slowing in older adults (Henry et al, 2015), or target location could contribute to higher ongoing task response times. Thus, eye tracking seems to have advantages over traditional ongoing task measures and can be a good way of better understanding monitoring behavior (see also Bowden et al, 2017;Chen et al, 2013;Shelton and Christopher, 2016). Yet, due to age-related changes in the anatomy of the eye (e.g., Salvi et al, 2006) as well as the greater need for glasses in the older sample, data quality was worse in the older adults compared to the younger ones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the content of visual stimuli, the distribution of visual attention, the testing conditions and the memory indicators are closely related. For instance, the distribution of visual fixations may be affected by the parallel implementation of two types of activity [9]. Emotionally significant stimuli attract longer visual fixations than neutral ones [10].…”
Section: Introductionmentioning
confidence: 99%